2022
DOI: 10.3390/insects13070643
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomics of Chinch Bugs from China and Implications for Its Coevolutionary Relationship with Grasses

Abstract: Blissidae (the Chinch bug) is a group with high species richness in Lygaeoidea, but there are only a few descriptions of mitochondrial genomes available. We obtained mitogenomes from 10 species of eight genera from Blissidae through second-generation sequencing technology. The length of the mitochondrial genome (excluding the control region) is between 14643 and 14385 bp; the content of AT is between 74.1% and 77.9%. The sequence of the evolution rate of protein coding genes was as follows: ND5 > ATP8 > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Mitogenomes are one of the most information-rich characteristics, and are useful in phylogeny, evolutionary history, species delimitation and population genetics [ 2 , 3 , 4 , 5 ]. Such studies have been well documented in many insect groups, and greatly contributed to understanding their phylogeny and evolution [ 6 , 7 , 8 , 9 ]. In Gryllotalpidae, however, only four species have available mitogenomes in GenBank to date [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitogenomes are one of the most information-rich characteristics, and are useful in phylogeny, evolutionary history, species delimitation and population genetics [ 2 , 3 , 4 , 5 ]. Such studies have been well documented in many insect groups, and greatly contributed to understanding their phylogeny and evolution [ 6 , 7 , 8 , 9 ]. In Gryllotalpidae, however, only four species have available mitogenomes in GenBank to date [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 8 species belong to Blissidae, 2 species belong to Colobathristidae and the remaining 3 species belong to Heterogastridae, Malcidae, and Berytidae, respectively. Blissidae species typically exhibit a narrow and flat body, predominantly feeding on Poaceae plants (Wang et al., 2022). They are commonly found in the sheaths of reeds ( Dimorphopterus japonicus (Hidaka, 1959)), wild rice ( Macropes raja Distant, 1909), sugarcane ( Cavelerius saccharivorus (Okajima, 1922)) and other Poaceae plants (Gao, 2010; Wang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Blissidae species typically exhibit a narrow and flat body, predominantly feeding on Poaceae plants (Wang et al., 2022). They are commonly found in the sheaths of reeds ( Dimorphopterus japonicus (Hidaka, 1959)), wild rice ( Macropes raja Distant, 1909), sugarcane ( Cavelerius saccharivorus (Okajima, 1922)) and other Poaceae plants (Gao, 2010; Wang et al., 2022). Consistent with our field observations, Blissidae species inhabit almost exclusively in bamboo sheaths (Slater & Brailovsky, 1983, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…More than a half of the Neotropical species of Ischnodemus are recorded from central and northeastern Argentina, mostly distributed in the Chaco and Pampa ecoregions where grasslands are abundant. A recent study on mitogenomes of 10 species in eight genera of Blissidae (Wang et al 2022) suggested that consistency of divergence time between Blissidae and Poaceae might hint at the co-evolutionary relationship between these families.…”
mentioning
confidence: 99%